2017
DOI: 10.3382/ps/pew459
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic and ACE-inhibitory activities of promod 278P hydrolysate of ovotransferrin from chicken egg white

Abstract: Peptides released from egg proteins via enzymatic hydrolysis show various bioactivities such as antimicrobial, antioxidant, antihypertensive, and immunomodulatory properties. The objective of this study was to investigate the cytotoxic and Angiotensin Converting Enzyme (ACE)-inhibitory activities of ovotransferrin and its promod 278P enzyme hydrolysate. Ovotransferrin from egg white was hydrolyzed using promod 278P at 45°C for 3 hours. Using the MTT assay, the cytotoxicity of ovotransferrin and promod 278P hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…This enzyme triggers the processing and activation of angiotensin I into the active vasoconstrictor angiotensin II. Several yolk-derived peptides bearing antihypertensive activities have been described in the literature [113,124] along with ovotransferrin and egg white hydrolysates [125,126]. Some of these peptides contain only three amino-acids [27,127].…”
Section: Egg Nutraceuticalsmentioning
confidence: 99%
“…This enzyme triggers the processing and activation of angiotensin I into the active vasoconstrictor angiotensin II. Several yolk-derived peptides bearing antihypertensive activities have been described in the literature [113,124] along with ovotransferrin and egg white hydrolysates [125,126]. Some of these peptides contain only three amino-acids [27,127].…”
Section: Egg Nutraceuticalsmentioning
confidence: 99%
“…Among the reported methods of hydrolyzing ovotransferrin, enzymatic hydrolysis was more widely used than other methods. Especially, commercially available plant, animal, and fungi or bacterial enzymes have been utilized with the enzyme-to-substrate ratio at 1:25 (Kim et al, 2012) and 1:50 (Moon et al, 2017). Single enzyme hydrolysis was the most commonly used method, but the use of two or more enzyme combinations also have been tested.…”
Section: Production Of Ovotransferrin-derived Functional Peptidesmentioning
confidence: 99%
“…The peptides produced from ovotransferrin using dilute acid hydrolysis (Ibrahim et al, 2000;Kim et al, 2012;Moon et al, 2013) or enzymatic hydrolysis (Huang et al, 2010;Keung et al, 1982;Kim et al, 2012;Lee et al, 2006;Lei et al, 2011;Ma et al, 2020;Moon et al, 2017;Shen et al, 2010;Wang et al, 2017) also have been reported to have antioxidant, antimicrobial, antihypertensive and anticancer properties. Hence, egg white ovotransferrin and its derived peptides may have great potentials to be used as antimicrobial and antioxidative agents in the food industry and anticancer, antiviral, antihypertensive, and metal-supplementing agents in the medical and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…An ovotransferrin peptide attenuates TNF-α-induced inflammation and superoxide generation in endothelial cells [ 112 ]. Hydrolyzates of ovotransferrin, as well as other egg white peptides, have also shown potent ACE inhibitory activity [ 79 , 80 ] and as is the case for bovine lactoferrin, an ovotransferrin peptide blocked angiotensin II effects via the angiotensin II receptor type 1 [ 81 ], thereby reducing inflammation potentiated by RAS activation. In an animal model study of peritonitis, ingestion of 40 mg/kg feed of an ovotransferrin peptide significantly attenuated the inflammatory responses: serum levels of TNF-α, IL-6 and myeloperoxidase activity were significantly reduced [ 82 ].…”
Section: Ovotransferrin As An Antiviral and Immune Modulatormentioning
confidence: 99%